A Review of Commercially Available Cellular-based Allografts. Issue 1 (February 2022) - Pinter, Zachariah W.; Elder, Benjamin D.; Kaye, I. David; Kepler, Christopher K.; Wagner, Scott; Freedman, Brett A.; Sebastian, Arjun S.
Abstract : Study Design: This was a narrative review. Objective: This review discusses our current knowledge regarding cellular-based allografts while highlighting the key gaps in the literature that must be addressed before their widespread adoption. Summary of Background Data: Iliac crest bone graft is the gold-standard bone graft material but is associated with donor site morbidity. Commonly utilized bone graft extenders such as demineralized bone matrix and bone morphogenetic protein have conflicting data supporting their efficacy and lack the osteogenic potential of new cellular-based allograft options. Methods: An extensive literature review was performed. The literature was then summarized in accordance with the authors' clinical experience. Results: There is not widespread evidence thus far that the addition of the osteogenic cellular component to allograft enhances spinal fusion, as a recent study by Bhamb and colleagues demonstrated superior bone formation during spine fusion in an aythmic rat model when demineralized bone matrix was used in comparison to Osteocel Plus. Furthermore, the postimplantation cellular viability and osteogenic and osteoinductive capacity of cellular-based allografts need to be definitively established, especially given that a recent study by Lina and colleagues demonstrated a paucity of bone marrow cell survival in an immunocompetent mouse posterolateral spinal fusion model. Conclusions: This data indicates that the substantially increased cost of these cellular allografts may not be justified. Level of Evidence: Level V.